Development of solar powered knapsack sprayer - SINHA, J P; SINGH, J K; KUMAR, ADARSH; AGARWAL, K N (The Indian Journal of Agricultural Sciences, 2018)
The small and marginal farmers in India are 83% with land holding of 46.1% and contribution of 51.2% in the production. On Indian farms, knapsack sprayers are very commonly used by small and marginal farmers for pest control because of affordability and ease of operation but with lower outputs. An attempt was made to develop a solar powered sprayer which had higher output (0.3 ha/hr) with lower physiological energy consumption and discomfort. An electronic control had been embedded for protection against deep discharge and over charging of battery for longer operational life. The system could be fully charged by solar energy within two hours of irradiation and can be operated continuously for six hours.This ensures quality spray with uniform droplet size in the swath. Anti-clogging filter had also been installed before the nozzle in nozzle head for trouble free operation as well as longer service life of nozzle.